Observational constraints on particle acidity using measurements and modelling of particles and gases. (22nd June 2017) - Murphy, J. G.; Gregoire, P. K.; Tevlin, A. G.; Wentworth, G. R.; Ellis, R. A.; Markovic, M. Z.; VandenBoer, T. C.
Abstract : In many parts of the world, the implementation of air quality regulations has led to significant decreases in SO2 emissions with minimal impact on NH3 emissions. In Canada and the United States, the molar ratio of NH3  : SO2 emissions has increased dramatically between 1990 and 2014. In many regions of North America, this will lead the molar ratio of NH x  : SO4, where NH x is the sum of particle phase NH4 + and gas phase NH3, and SO4 is the sum of particle phase HSO4 − and SO4 2−, to exceed 2. A thermodynamic model (E-AIM model II) is used to investigate the sensitivity of particle pH, and the gas-particle partitioning of NH x and inorganic nitrate, to the atmospheric NH x  : SO4 ratio. Steep increases in pH and the gas fraction of NH x are found as NH x  : SO4 varies from below 1 to above 2. The sensitivity of the gas fraction of nitrate also depends strongly on temperature. The results show that if NH x  : SO4 exceeds 2, and the gas and particle phase NH x are in equilibrium, the particle pH will be above 2. Observations of the composition of particulate matter and gas phase NH3 from two field campaigns in southern Canada in 2007 and 2012 have median NH x  : SO4 ratios of 3.8 and 25, respectively. These campaigns exhibited similar amounts of NH3, but very different particle phase loadings. Under these conditions, the pH values calculated using the observations as input to the E-AIM model were in the range of 1–4. The pH values were typically higher at night because the higher relative humidity increased the particle water content, diluting the acidity. The assumption of equilibration between the gas and particle phase NH x was evaluated by comparing the observed and modelled gas fraction of NH x . In general, E-AIM was able to reproduce the partitioning well, suggesting that the dominant constituents contributing to particle acidity were measured, and that the estimated pH values were realistic. These results suggest that regions of the world where the ratio of NH3  : SO2 emissions is beginning to exceed 2 on a molar basis may be experiencing rapid increases in aerosol pH of 1–3 pH units. This could have important consequences for the rates of condensed phase reactions that are acid-catalyzed.